The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1053/seiz.2002.0676
|View full text |Cite
|
Sign up to set email alerts
|

Source analysis of polyspike and wave complexes in juvenile myoclonic epilepsy

Abstract: We applied dipole modeling and brain distributed source analysis to find current sources comprising spikes and slow waves of polyspike and wave complexes (PSWC) in patients with juvenile myoclonic epilepsy (JME). The dipoles were localized in frontal, parietal and temporal lobes. The frontal dipoles were clustered in the frontal medial gyrus and fronto-orbital region. A midsagittal frontal current source was observed using brain distributed source analysis in all patients. When the slow wave was analyzed, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…In one study, asymmetry of the epileptiform discharges on scalp EEG pointed towards potentially different seizure onset as the etiology of AED resistance in patients with juvenile myoclonic epilepsy (JME), an idiopathic generalized epilepsy syndrome (11); patients with asymmetric GSWD are much more likely to have R-IGE (1, 11). Studies utilizing dipole modeling showed widespread cortical (predominantly frontal) GSWD onset in patients with IGEs (medication response not provided) (12, 13) and corroborated the evidence from morphometric studies suggestive of frontal cortical anatomical abnormalities in patients with IGEs (14, 15). Similarly, recent magneto-encephalographic (MEG) source analysis in patients with predominantly R-IGEs showed localization of the GSWD generators mainly in the central and premotor regions of the frontal lobes (16).…”
Section: Introductionsupporting
confidence: 56%
“…In one study, asymmetry of the epileptiform discharges on scalp EEG pointed towards potentially different seizure onset as the etiology of AED resistance in patients with juvenile myoclonic epilepsy (JME), an idiopathic generalized epilepsy syndrome (11); patients with asymmetric GSWD are much more likely to have R-IGE (1, 11). Studies utilizing dipole modeling showed widespread cortical (predominantly frontal) GSWD onset in patients with IGEs (medication response not provided) (12, 13) and corroborated the evidence from morphometric studies suggestive of frontal cortical anatomical abnormalities in patients with IGEs (14, 15). Similarly, recent magneto-encephalographic (MEG) source analysis in patients with predominantly R-IGEs showed localization of the GSWD generators mainly in the central and premotor regions of the frontal lobes (16).…”
Section: Introductionsupporting
confidence: 56%
“…Source localization utilizing MEG has identified frontal lobe localizations in people with IGE (35, 36). In people with juvenile myoclonic epilepsy, spike-and-slow wave discharges were modeled to the medial prefrontal region (35). An EEG-fMRI study of a patient with IGE revealed frontal deactivation during a generalized spike-wave discharge (37).…”
Section: Discussionmentioning
confidence: 99%
“…A study of dipole source localization with polyspike and wave complexes in JME patients reported that the dipoles of the polyspike component are located in the medial frontal gyrus, and suggested that this region contains hyperexcitable neurons [15]. In a [ 11 C]flumazenil (FMZ) PET study, a significantly higher mean [ 11 C]FMZ volume of distribution (FMZVD) in the cerebral cortex was reported, and it was suggested that increased FMZVD could reflect microdysgenesis or a state of cortical hyperexcitability [22]. In addition, another study reported mildly increased rCBF in the superior frontal area of JME patients [26].…”
Section: Discussionmentioning
confidence: 99%